Post-Stress Block of Kappa Opioid Receptors Rescues Long-Term Potentiation of Inhibitory Synapses and Prevents Reinstatement of Cocaine Seeking - Polter, Abigail M. (Biol Psychiatry, 2014)
BACKGROUND: Dopaminergic neurons in the ventral tegmental area (VTA) of the brain are an important site of convergence of drugs and stress. We previously identified a form of long-term potentiation of GABAergic synapses on these neurons (LTP(GABA)). Our studies have shown that exposure to acute stress blocks this LTP, and that reversal of the block of LTP(GABA) is correlated with prevention of stress-induced reinstatement of cocaine-seeking. METHODS: Sprague-Dawley rats were subjected to cold-water swim stress. Midbrain slices were prepared following stress, and whole-cell patch clamp recordings of IPSCs were performed from VTA dopamine neurons. Antagonists of glucocorticoid and kappa opioid receptors were administered at varying time points after stress. Additionally, the ability of a post-stress kappa antagonist to block FSS-induced reinstatement of cocaine self-administration was tested. RESULTS: We report that an acute stressor blocks LTP(GABA) for five days after stress through a transient activation of glucocorticoid receptors and more lasting contribution of kappa opioid receptors. Pharmacological block of kappa opioid receptors beginning as late as 4 days after stress has occurred can reverse the block of LTP(GABA). Furthermore, post-stress administration of a kappa opioid antagonist prevents reinstatement of cocaine-seeking. CONCLUSIONS: Our results show that a brief stressor can cause days-long changes in the reward circuitry and reveal roles for glucocorticoid and kappa opioid receptors as mediators of the lasting effects of stress on synaptic plasticity. These results indicate that kappa opioid receptor antagonists reverse the neuroadaptations underlying stress-induced drug-seeking behavior and may be useful in the treatment of cocaine addiction.